Consuming K-Pop Photocards: Mediated Intimacy in Indonesian Fan Practices - Kitra Desnika; Shuri Mariasih Gietty Tambunan (CV. Media Digital Publikasi Indonesia, 2023)
K-Pop fans’ consumptive behavior is reflected through the act of a variety of K-Pop merchandise and one of these merchandises is photocards. This article highlights photocards as a microscopic case study to explore the problematic fan practice of humanizing these photocards particularly as fans post contents related to their photocards on social media. Fans who actively collect K-Pop photocards treat them as if they are a substitute of their idols and they need to be always protected with care. Research findings show that fans treat photocards as a living human being for example by bringing these photocards while they do their activities and addressing them in their social media posts reflecting an intimate relationship between fans and the imagined presence of their idols through the photocards. By utilizing content analysis and ethnography method, data were collected through TikTok and interview session with several respondents (K-Pop photocard collectors). This research aims to observe how photocard is not only a material object that is meaningless. These photocards are humanized like a friend and become a replacement from the absence of the real form of the idols. Photocards’ meaning making process is dynamic while reflecting fans’ behavior in the context of K-Pop fandom in Indonesia